Evaluación de la gestión de control interno en la Ejecución presupuestal de la Universidad Nacional de San Martín, periodo 2014 - Pérez Corrales, Juliet Dianita (2016)
The Research "Management Assessment of Internal Control in Budget Execution of the National University of San Martin, period 2014", aims to evaluate the management of Internal Control in Budget Execution of UNSM" investigation by the type, applicative; depending on the level of research is explanatory and exploratory; collection and analysis of data is qualitative and quantitative. It was taken as population workers in the headquarters of the National University of San Martin, totaling 128, with the shows a total of 96 workers. After applied the methodological process and analyzed the results obtained arrive at the following conclusions: (i) The management evaluation Internal Control in Budget Execution of UNSMs, period 2014 shows that there are gaps to reach the level of satisfactory and the Internal Control of the budgetary Framework reached a satisfactory level of 60.0%, the Internal Control programming Budget Execution 71.4%; Internal Control Assessment Budget 17.0% and 55.0% Internal Accounting Control. (Ii) The level of knowledge of the legal aspects of the Internal Control Standards and its relation to the budget execution reached 87.5%. (Iii) The main organizational deficiencies related to Internal Control Standards relate to the planning of internal control it is poor, and focuses only on an almost exclusive work of auditors and authorities; and (iv) Progress in the budget execution for 2014 was 94.4% for all generic spending, which is considered an optimum value.